A Four Novel Energy Pattern Factor Method for Computation of Weibull Parameter in Impact Strength Reliability of Fibre-Reinforced Concrete - R, Gayathri; G, Murali.; Kathirvel, Parthiban; M.K, Haridharan; K, Karthikeyan. (International Journal of Engineering and Technology, 2018)
Impact strength data is a noteworthy factor for designing airport pavements, civilian and military structures etc and it is ought to be modelled precisely. In order to achieve an appropriate modelling data, it is important to select a suitable estimation method. One such commonly used statistical tool is the two parameter Weibull distribution for modelling impact failure strength accurately besides the variations in test results. This study statistically commandsthe variations in the impact failure strength (number of blows to induce failure) of fibre reinforced concrete (FRC) subjected to drop hammer test. Subsequently, a four-different novel method for the computation of Weibull parameter (Shape parameter) based on the earlier researchers test results has been proposed. The accuracy of the proposed four novel method is demonstrated by comparing with power density method and verified with goodness of fit test. Finally, the impact failure strength of FRC is offered in terms of reliability. The proposed four NEPFM is very suitable and efficient to compute the shape parameter in impact failure strength applications.Â